In-situ deposition of three-dimensional graphene on selective laser melted copper scaffolds for high performance applications. (August 2020) - Cheng, Kaka; Xiong, Wei; Li, Yan; Hao, Liang; Yan, Chunze; Li, Zhaoqing; Liu, Zhufeng; Wang, Yushen; Essa, Khamis; Lee, Li; Gong, Xin; Peijs, Ton
Abstract: Currently, three-dimensional graphene (3DG) fabrication was restricted by the complicated process, strict chemical reactions as well as structural accuracy. Herein we creatively propose a bottom-up strategy that leverages the selective laser melting (SLM) technique to manufacture a three-dimensional (3D) porous copper template. Graphene was then in-situ grown via chemical vapor deposition (CVD) on the obtained porous Cu template, forming 3DG composites. A combination of conventional graphene growth via CVD technique with SLM fabricated scaffold templates enabled an accurate design and regulation of 3DG from macro-structure (unit type, porosity, aperture) to micro-structure (texture, surface quality) through an elaborately manipulated porous copper scaffold. The 3DG/copper scaffold could achieve around 88% and 27% enhancement in electromagnetic interference (EMI) shielding and thermal diffusion, respectively. Particularly, the highest EMI shielding efficiency ( SE ) can reach up to 47.8 dB at 2.7 GHz and exhibit an average SE of 32.3 dB at the range of 2–18 GHz. The synergistic shielding mechanisms accounted for the improvement derived from the use of hybrid composite materials and precise architecture of the SLM porous structure.